2008
DOI: 10.1159/000157873
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Growth during the First Years of Life: What Is Normal?

Abstract: The anthropometric data of a longitudinal growth study on healthy infants, followed from birth until the age of 4 years and performed during 1995–1999 in The Netherlands, were used to analyze the general growth patterns in terms of height, weight and head circumference, based on z-scores, during the first 4 years of life. The well-known phenomenon where each infant or child tends to decelerate or accelerate its growth velocity depending on its starting position on the reference curve is obvious in this study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In contrast, we suggest that 'convergence' may involve sites of methylation equalization between co-twins, possibly reflecting regression to the mean as a contributing factor. Regression to the mean is a phenomenon in which it is a statistical certainty that individual phenotypes, such as growth patterns [67], shift to the population mean over time [68]. This explains why twins with birth weight discordance become more similar over time [69] and can be understood in terms of twin-specific uterine-specific restrictions being replaced postnatally by a greater degree of shared environment [69-71].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we suggest that 'convergence' may involve sites of methylation equalization between co-twins, possibly reflecting regression to the mean as a contributing factor. Regression to the mean is a phenomenon in which it is a statistical certainty that individual phenotypes, such as growth patterns [67], shift to the population mean over time [68]. This explains why twins with birth weight discordance become more similar over time [69] and can be understood in terms of twin-specific uterine-specific restrictions being replaced postnatally by a greater degree of shared environment [69-71].…”
Section: Discussionmentioning
confidence: 99%
“…The model used in the current study to predict z‐scores in each child is based on findings showing that children follow their own growth curve from approximately 1 to 1.5 years until puberty. Several studies demonstrated that in the period between infancy and puberty children kept their own growth curve; whereas in infancy and puberty z‐scores deviated considerably . Another study found horizontal height tracks in a majority of pre‐pubertal children, indicating that those children maintained their growth curve.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy children follow their individual growth curve until puberty . In case of normal growth, data from the individual growth curve can be used to predict future weight and height . This study has two main objectives: First, we aimed to compare actual weight and height at diagnosis with predicted weight and height based on the child's growth curve.…”
Section: Introductionmentioning
confidence: 99%
“…Infants at the extremes of the birth weight distribution tend to display catch-up or catch-down growth according to birth weight during the first year (Touwslager et al, 2008). Infants at the extremes of the birth weight distribution tend to display catch-up or catch-down growth according to birth weight during the first year (Touwslager et al, 2008).…”
mentioning
confidence: 99%
“…Much recent research has focused on early postnatal growth as mediating the relationship between birth weight and subsequent risk. Infants at the extremes of the birth weight distribution tend to display catch-up or catch-down growth according to birth weight during the first year (Touwslager et al, 2008). Accelerated growth among smaller infants predicts long-term changes in neuroendocrine function (Savino et al, 2005;Patel and Srinivasan, 2010), obesity (Stettler et al, 2002;Dennison et al, 2006), and other aspects of metabolic risk (Singhal and Lucas, 2004).…”
mentioning
confidence: 99%